The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2340/00015555-0931
|View full text |Cite
|
Sign up to set email alerts
|

High Body Mass Index in Adolescent Girls Precedes Psoriasis Hospitalization

Abstract: Psoriasis is associated with being overweight, but the temporal relationship is not known. This historical cohort study tested whether severe psoriasis resulting in hospitalization in adulthood was preceded by excess increase in age-adjusted body mass index, a known risk factor in childhood for being overweight in adulthood. The study cohort was based on the Copenhagen School Health Records Register, birth years 1930 to 1984 (309,152 schoolchildren). Cases were found through the Danish National Patient Registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 57 publications
(50 reference statements)
0
29
0
2
Order By: Relevance
“…[6][7][8][9][10][11][12][13]15 Obesity apparently predisposes to the development of psoriasis and vice versa, although there is less evidence for the latter. [6][7][8][9][10][11][12][13]15 Two studies have provided results suggesting that patients with psoriasis gain weight after the onset of the condition. Herron et al 32 presented retrospective data from 557 patients with psoriasis and concluded that obesity did not seem to have a role in the onset of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13]15 Obesity apparently predisposes to the development of psoriasis and vice versa, although there is less evidence for the latter. [6][7][8][9][10][11][12][13]15 Two studies have provided results suggesting that patients with psoriasis gain weight after the onset of the condition. Herron et al 32 presented retrospective data from 557 patients with psoriasis and concluded that obesity did not seem to have a role in the onset of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In addition, epidemiological studies have established that psoriasis is associated with obesity and that increased adiposity and weight gain are risk factors for incident psoriasis. [6][7][8][9][10][11][12][13][14][15] Like psoriasis, obesity is accompanied by low-grade systemic inflammation, and, theoretically, obesity-induced proinflammatory mechanisms may exacerbate psoriatic lesions in overweight patients with psoriasis. 16 At present, the role of weight loss as a treatment for psoriasis in obese patients is unclear, but it is reasonable to assume that weight loss in such patients may reduce the obesity-induced inflammation, which may in turn improve the skin disease.…”
mentioning
confidence: 99%
“…Weight gain from the age of 18 years, higher waist circumference, hip circumference, and waist-hip ratio were all associated with a higher risk of incident psoriasis [40] . In 2010, Bryld et al [41] conducted a study exploring the temporal relationship between obesity and psoriasis. The study cohort included 309,152 school children and found that, for women, severe psoriasis resulting in hospitalization in adulthood was preceded by an increased BMI at the age of 12.…”
Section: Association Between Psoriasis and Obesitymentioning
confidence: 99%
“…Others include calcium channel blockers, interferon, terbinafine, diazepam, and antibiotics (especially tetracycline). [35][36][37][38] weight A prospective study by Setty et al 39 suggested that women with a higher body mass index (BMI) were more prone to psoriasis; this finding was confirmed by a study by Bryld et al 40 Zhang et al studied 4,452 subjects with psoriasis vulgaris and 1,166 healthy individuals, and found that overweightness and obesity occurred in 23% and 4% of subjects with psoriasis, respectively, which was significantly higher than controls. Severity of psoriasis and Psoriasis Area and …”
Section: Drugsmentioning
confidence: 98%